Comparative assessment of soft-tissue changes in Class II Division 1 patients following extraction and non-extraction treatment - Sneh Lata Verma; Vijay Prakash Sharma; Gyan Prakash Singh; Kiran Sachan (Wolters Kluwer Medknow Publications, 2013)
Background: The extraction of teeth for orthodontic purpose has always been a controversial subject in the speciality. The aesthetics impact of the soft-tissue profile might play a key role in deciding on premolar extraction or non-extraction (NE) treatment, particularly in borderline patients. The purpose of this cephalometric study was to examine the soft-tissue treatment effects of Class II Division 1 malocclusion undergoing extraction of all first premolars in comparison with patients undergoing treatment with a NE approach. Materials and Methods: Hundred post-pubertal female patients of Class II Division 1 malocclusion were selected. Group 1, treated with four first premolar extractions, consisted of 50 female patients with a mean age of 14 years 1 month. Group 2, treated without extractions, consisted of 50 patients with a mean age of 13 years 5 months. Pre-treatment and post-treatment lateral cephalograms of the patients were obtained. The pre-treatment and post-treatment stage comparison and the intergroup comparison of the treatment changes were conducted between extraction and NE groups of Class II malocclusion samples with t tests. The levels of significance tested were P < 0.05 and P < 0.01. Results: The main soft-tissue differences between the groups at the end of treatment were a more retruded lower lip and a more pronounced lower labial sulcus in those patients subjected to extraction. Conclusion: In Class II Division 1 patients, the extraction or NE decision, if based on sound diagnostic criteria, seems to have no systematic detrimental effects on the facial profile.